PERAN KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) KARYA USAHA MANDIRI (KUM) BOGOR CABANG SUKARAJA DALAM MENGEMBANGKAN SUMBER DAYA INSANI YANG BERAKHLAK MULIA - Alfiansyah; Thantawi, Tubagus Rifqy; Putra, Bayu Purnama (SAHID BANKING JOURNAL, 2023)
This study discusses the "role of companies in developing human resources with noble character" which aims to, (1) To analyze the role of companies in forming and developing human resources with noble character and (2) To analyze the performance of HRD with noble character towards the responsibility that provided by the company. This research was conducted at the Savings and Loans Financing Cooperative (KSPPS) KUM Bogor Sukaraja branch, as for the number of interviewees who interviewed there were 7 (seven) respondents. The analytical method used is descriptive analysis. This study uses descriptive qualitative analytical research methods with interview techniques, observation, documentation and data collection from related sources (books and the internet). The results of this study indicate that there is a positive influence in the moral development of employees at KSPPS KUM Bogor Sukaraja branch. This is evidenced from interviews conducted with customers who joined the Sukaraja branch of KSPPS KUM Bogor.